Toward Equitable Digital Mental Health: Integrating AI and Telepsychiatry in Global Practice - Algristian, Hafid; Sitorus, Anwar T (Digitus : Journal of Computer Science Applications, 2024)
In response to the growing mental health crisis and the expansion of digital healthcare, this narrative review explores the application of telepsychiatry and artificial intelligence (AI) in mental health services. The study aims to synthesize recent developments, challenges, and future directions in digital mental health innovation. A systematic literature search was conducted across PubMed, Scopus, and Web of Science databases, focusing on studies published between 2016 and 2023. Keywords such as "telepsychiatry," "mental health," "artificial intelligence," and "technology adoption" were used to identify relevant empirical and theoretical works. Inclusion criteria emphasized real-world applications and stakeholder perspectives. The results reveal substantial variability in the understanding and implementation of telepsychiatry across different regions and populations. Socioeconomic factors, digital literacy, and cultural perceptions significantly influence the acceptance and success of digital interventions. While AI-driven tools improve diagnostic efficiency and reduce treatment delays, systemic barriers such as regulatory limitations, institutional resistance, and data privacy concerns impede widespread adoption. Comparative analysis highlights a more favorable reception in high-income countries, though underserved populations in both developed and developing nations continue to face accessibility challenges. These findings underscore the urgent need for inclusive policies, capacity-building initiatives, and ethical AI governance frameworks. Addressing these factors can bridge existing gaps and ensure more equitable mental healthcare. The study concludes by emphasizing the importance of sustained interdisciplinary research to refine telepsychiatric models and promote socially responsible technology integration.